Medium, Messenger, Transmission An Approach to Media Philosophy - Krämer, Sybille (Recursions, 2015)
This rich study provides a comprehensive introduction to media philosophy while offering a new perspective on the concept and function of transmission media in all systems of exchange. Krämer uses the figure of the messenger as a key metaphor, examining a diverse range of transmission events, including the circulation of money, translation of languages, angelic visitations, spread of infectious diseases, and processes of transference and counter-transference that occur during psychoanalysis."'An interesting read, with an incorporated overview of media theory." - Ana Peraica, Leonardo Reviews